Water Quality Analysis In Bengawan Solo River Bojonegoro Regency - Dyah Setyaningrum; Laily Agustina Rahmawati (Faculty of Science and Technology University Ibrahimy, 2020)
The purposeofthis research is to analyze the water quality of Bengawan Solo River in Bojonegoro Regency. Water sampling was carried out at 6 monitoring points along the Bengawan Solo River in Bojonegoro Regency. Determination of sampling monitoring points, based on the differences of characteristics that exist in the study area. Some parameters issued are temperature, conductivity, COD, BOD, and Oil/ fat food which are then compared with the criteria for Class III standards of river water quality in accordance with the Regional Regulation of East Java Province Number 2 of 2008. Based on the analysis results obtained at each point monitor, area 1, is the most polluted area. It is caused, in this area, there are several activity of downtown. Households produce waste from bathroom, toilet, kitchen, washing clothes and washing household appliances.